Hydroethanolic Extract of A. officinarum Hance Ameliorates Hypertension and Causes Diuresis in Obesogenic Feed-Fed Rat Model - Javaid, Farah; Mehmood, Malik Hassan; Shaukat, Bushra (Frontiers in Pharmacology, 2021)
Alpinia officinarum has been used widely in traditional Chinese and Ayurvedic medicines. Its folkloric uses include relieving stomach ache, treating cold, improving the circulatory system, and reducing swelling. Its effectiveness and mechanism of antihypertension in obesity-induced hypertensive rats have not been studied yet as per our knowledge. This study has been designed to provide evidence of underlying mechanisms to the medicinal use of A. officinarum as cardiotonic using obesity-induced hypertension model in rats. Chronic administration of A. officinarum caused a marked reduction in the body weight gain and lee index of rats compared to the obesogenic diet-fed rats. Its administration also caused attenuation in blood pressure (systolic, diastolic, and mean) serum total cholesterol, triglyceride, and leptin, while an increase in serum HDL and adiponectin levels was noticed. The catalase and superoxide dismutase enzymatic activities were found remarkable in the serum of A. officinarum treated animal groups. A. officinarum showed mild to moderate diuretic, hepatoprotective, and reno-protective effects. A. officinarum treated group showed less amount of mRNA expression of 3-hydroxy-3-methylglutaryl-CoA reductase while the mRNA expression of Peroxisome proliferator-activated receptor and mRNA expression of Cholesterol 7 alpha-hydroxylase was raised in comparison to the hypertensive group of rats evaluated by quantitative real-time polymerase chain reaction. These findings show that A. officinarum possesses antihypertensive and diuretic activities, thus providing a rationale to the medicinal use of A. officinarum in cardiovascular ailments.